RESEARCH ON PHYSICAL AND MECHANICAL PROPERTIES OF POLYVI-NYL ACETATE-BASED (PVA) ADHESIVE COMPOSITION - Kshyvetskyy , Bogdan (Forestry, Forest, Paper and Woodworking Industry, 2024)
Findings of research on temperature and humidity load of PVA-based adhesive film were provided and its influence on the change in physical and mechanical properties of adhesive composition was determined.